A randomized trial to assess the efficacy of interferon alpha in combination with ribavirin in the treatment of interferon alpha nonresponders with chronic hepatitis C: superior efficacy of high daily dosage of interferon alpha in genotype 1 - Tassopoulos, N. C.; Tsantoulas, D.; Raptopoulou, M.; Vassiliadis, T.; Kanatakis, S.; Paraskevas, E; Vafiadis, I.; Avgerinos, A.; Tzathas, C.; Manolakopoulos, S.; Ketikoglou, I.; Aggelis, P.; et al. (J Viral HepatJ Viral HepatJ Viral Hepat, 2003)
A randomized trial was conducted to assess the efficacy of daily (QD) or thrice weekly (TIW) administration of interferon-alpha (IFN) in high doses in combination with ribavirin (1.0-1.2 g/day) in patients with chronic hepatitis C (CHC) who were nonresponders to previous IFN monotherapy. Interferon was administered as 10 MU IFN (QD or TIW) for 4 weeks, followed by 5 MU IFN (QD or TIW) for 20 weeks, and then by 3 MU IFN (QD or TIW) for 24 weeks. Sustained virological response (SVR) was evaluated in 142 patients who received at least one dose of medication. One-fourth of the patients achieved SVR, 26% of those treated with IFN QD and 25% of those treated with IFN TIW (P = 0.85). For genotype 1 patients, SVR rates were 32.4 and 15.8% for IFN QD and IFN TIW, respectively, whereas for genotype non-1 patients the corresponding SVR rates were 20.6 and 36.4%, respectively (test of homogeneity: P = 0.031). This finding was further confirmed by multivariate logistic regression analysis where a statistically significant interaction (P = 0.012) was found between treatment and HCV genotype indicating that the IFN QD regimen was superior to IFN TIW among genotype 1 patients whereas, among genotype non-1 patients, the two treatments were similar (odds ratio of SVR in IFN QD vs IFN TIW: 3.33 among genotype 1 patients, 95% CI: 1.00-11.14). In conclusion, re-treatment of patients not responding to previous IFN monotherapy with a combination of high daily dose of IFN with ribavirin may be beneficial for genotype 1 infected patients.
Keywords: Adolescent; Adult; Aged; Antiviral Agents/administration & dosage/*therapeutic use; Drug Therapy, Combination; Female; Hepacivirus/classification/drug effects/genetics; Hepatitis C, Chronic/*drug therapy/virology; Humans; Interferon alpha-2; Interferon-alpha/administration & dosage/*therapeutic use; Male; Middle Aged; Recombinant Proteins; Ribavirin/administration & dosage/*therapeutic use; RNA, Viral/blood; Treatment Outcome